The 2022 Copyright Amendment Bill: Implications for the South African universities’ research economy - Keyan Tomaselli (Communicare)
The South African Copyright Amendment Bill of 2017 was passed in 2022. In justifying the weakening of copyright protections with regard to the educational arena, the Bill’s proponents have largely applied rhetorical discourses published in the popular media, also aggressively propagated at their public meetings. In contrast, the publishing industry has generated many hundreds of pages of economic impact studies supported by detailed legal arguments with reference to global treaties. My analysis assesses the different positions taken by the pro-Bill lobby, ReCreate, in comparison to the Copyright Coalition that questions the importation of an American fair use doctrine. The potential implications of the Bill for South African authors and artists operating in the educational environment are described. Since the object of study has been a moving target, and still was at the time of submission of this article, the conclusions that arise out of the ongoing debates are tentative – but prescient for the current conjuncture. The analysis relies on cross-referencing stakeholder submissions, newspaper articles and statements made by all parties to the discussion. In addition, a number of rejoinders were invited, which are published below. The study reveals the stark contradictions within emerging state policy relating to the creative industries in an era when information has economic value.